A prototype RC boat - Yong, Jason (2016)
Remote Controlled (RC) vehicles have evolved since Nikola Tesla showcased the first RC boat during an exhibition in 1898. The usage of RC boat has been wide, in many areas such as fishing and military. However, the potential of its usage as an educational tool remains largely unexplored. This project thus aims at constructing a prototype RC boat for this purpose. This report covers the work done throughout the course of the project. With several considerations in mind, the project begins with the designing of the prototype using a Computer Aided Design (CAD) software. The prototype was then built based on the design. Problems were identified in the first two designs, leading to the improvements on the final design. A do-it-yourself controller for the prototype was built using a transceiver module. The controller, which functions similar to a conventional transmitter, will enhance the learning experience. Simple programming was written into microcontroller for the controlling of both the prototype and the controller. The step-by-step procedure of the building phase was then documented.